Disobedience of Reason: The Body and Its Pleasures in a Delicious Novel by Arturo Arias, Sopa de caracol - Siu, Oriel María (2016)
This article examines how laughter, language, pleasure, the overflow of emotions and the senses, travestism, and desire appear in Arturo Arias’ Sopa de caracol (2002) as ungovernable zones where power and coloniality cannot reign. These are sites where power works alternatively, differing from what is usually seen within Central American diasporic and post-war textualities. In this novel power interrogates and inverts heterarquical models of power primarily acting in the absence of patterns that perpetuate the racialized superiority/inferiority structures posed by modernity/coloniality. Moreover, in this novel power acts within the parameters of a corpo-política, perspective from which epistemic practices of power that separate body from reason become subverted. These ungovernable jurisdictions and zones are the focus of the present article.